2014
DOI: 10.1177/230949901402200317
|View full text |Cite
|
Sign up to set email alerts
|

Curettage and Reconstruction by the Sandwich Technique for Giant Cell Tumours around the Knee

Abstract: Intralesional curettage, use of phenol, and reconstruction with allograft, gel foam, and cement (the sandwich technique) for GCT of bone achieved good functional outcome and a low recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
0
26
0
4
Order By: Relevance
“…12 The results of curettage have improved with the advent of extended curettage that uses adjuvants like liquid nitrogen, phenol, alcohol, hydrogen peroxide, zinc chloride, electrocoagulation, polymethyl methacrylate, and locally delivered chemotherapy. 1,20 The aim of extended curettage is to take care of microscopic tumor remnants in the walls, after the cavity is curetted out thoroughly. In literature, the incidence of local recurrence after simple curettage and bone grafting has been reported to be between 25 and 50% that has been dramatically reduced to 6 to 25% with the use of adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…12 The results of curettage have improved with the advent of extended curettage that uses adjuvants like liquid nitrogen, phenol, alcohol, hydrogen peroxide, zinc chloride, electrocoagulation, polymethyl methacrylate, and locally delivered chemotherapy. 1,20 The aim of extended curettage is to take care of microscopic tumor remnants in the walls, after the cavity is curetted out thoroughly. In literature, the incidence of local recurrence after simple curettage and bone grafting has been reported to be between 25 and 50% that has been dramatically reduced to 6 to 25% with the use of adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this facilitates the use of PMMA to achieve extended curettage by its thermal effect and hypoxic effect of its monomer while the articular cartilage degradation and subsequent sequelae are protected against. In their review of 36 cases using the Sandwich technique, Saibaba et al reported a very low recurrence rate of 2.8% and a good functional outcome of 92.3% of their patients at a single institution (5). In their practice and utilization of the Sandwich technique, two adjuvants in the form of bone cement and phenol were utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages of use of bone cement is that the heating effect destroys tumour cells and also helps in the early detection of recurrence indicated by the development of lucency at the cement bone interface but it has been associated with anaphylactic reactions and degeneration of the articular cartilage [3,19,20]. The sandwich technique of applying a layer of bone graft and gel foam protects the articular cartilage from the thermal effect of the bone cement and also gives support to the weakened subchondral area [4,21]. The advantage of allograft is that it incorporates well and there is no need for removal but it makes detection of recurrence difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of allograft is that it incorporates well and there is no need for removal but it makes detection of recurrence difficult. The requirement and maintenance of a bone bank is also a disadvantage [21]. The only patient that could afford a preoperative CT evaluation was the 14year old with simple bone cyst.…”
Section: Discussionmentioning
confidence: 99%